Macroeconomic policy and economic interdependence - Hodgman, Donald (ed.); Wood, Geoffrey Edward (New York : St. Martin's Press, 1989)
The papers collected in this volume examines various aspects of the conduct and consequences of national macroeconomic policy in a world of economically interdependent countries.
Includes bibliographies and index.
ijb, 15/01/2019
Loans
Keywords: Economic policy; International economic relations; Foreign exchange